Epidemiology and laboratory diagnosis of fungal corneal ulcer in the Sundarban Region of West Bengal, eastern India - Bandyopadhyay, S; Das, D; Mondal, KK; Ghanta, AK; Purkait, SK; Bhaskar, R (Nepalese Journal of Ophthalmology, 2012)
Introduction: Corneal ulcers are the second most-common cause of preventable blindness after cataract in tropical developing countries. Fungal corneal ulcers constitute 30 to 62 % of the total microbial culture-positive corneal ulcers. Objective: To study the epidemiological characteristics, risk factors and laboratory diagnosis of fungal corneal ulcer in the Sundarban Region, West Bengal, eastern India. Materials and methods: A retrospective review of 399 culture-positive, fungal corneal ulcers out of a total 928 corneal ulcer patients attending a tertiary care hospital in Kolkata, eastern India, over a period of four years from February 2007 to January 2011. Results: Males (246; 61.65 %) were more commonly affected than females (P < .0001). The affected people were mostly (342; 85.71 %) residing in the rural areas (P < .0001). 196 patients (49.12 %) were involved in agricultural activities (P < .0001). The younger people of, 21 - 50 years of age, were particularly prone to this disease (269; 67.41 %). Corneal trauma (354; 88.72 %) was the commonest risk factor (P < .0001) and 261 patients (61.41 %) had a history of trauma with vegetative matter (P< .0001). The use of topical corticosteroids was implicated in 65 (16.29 %) cases. The incidence of the disease was highest in the monsoon season, between June to September (192; 48.12 %). The aspergillus spp was the most common fungal growth (151; 37.84 %), followed by an Fusarium spp (81; 20.3 %). Conclusion: The fungal corneal ulcers are an important cause of ocular morbidity in people residing in the Sundarban Region. The identification of the etiology and the predisposing factors of corneal ulcers in this region are important for the prevention and early treatment of the disease. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5847 NEPJOPH 2012; 4(1): 29-36